Cardiac Networks United: an integrated paediatric and congenital cardiovascular research and improvement network. (20th December 2018) - Gaies, Michael; Anderson, Jeffrey; Kipps, Alaina; Lorts, Angela; Madsen, Nicolas; Marino, Bradley; Costello, John M.; Brown, David; Jacobs, Jeffrey P.; Kasnic, David; Lihn, Stacey; Lannon, Carole; et al.
Abstract: Optimising short- and long-term outcomes for children and patients with CHD depends on continued scientific discovery and translation to clinical improvements in a coordinated effort by multiple stakeholders. Several challenges remain for clinicians, researchers, administrators, patients, and families seeking continuous scientific and clinical advancements in the field. We describe a new integrated research and improvement network – Cardiac Networks United – that seeks to build upon the experience and success achieved to-date to create a new infrastructure for research and quality improvement that will serve the needs of the paediatric and congenital heart community in the future. Existing gaps in data integration and barriers to improvement are described, along with the mission and vision, organisational structure, and early objectives of Cardiac Networks United. Finally, representatives of key stakeholder groups – heart centre executives, research leaders, learning health system experts, and parent advocates – offer their perspectives on the need for this new collaborative effort.